Analyze the Relationship Between Monetary Policy and the Economics Growth of Lao PDR - SISANGA, Bouapheng; CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research study aims to analyze the relationship between monetary policy and the economic growth of the Lao PDR. The variables of the monetary policy include the loan interest rate (R) and the money supply (M2). This study focuses on analyzing the relationship with regression model, short-run correlation by the VECM model, long-run relationship (Cointegration) and analysis of cause and effect by the granger method. The research results show that: the analysis of the regression model show that the loan interest rate (LnR) has a negative effect on the economic growth of the Lao PDR with a statistical significance level of 0.05. For the money supply (LnM2) has no effect on the economic growth of the Lao PDR. For the short-run relationship analysis, it was found that the loan interest rate (LnR) has a relationship with the economic growth of Lao PDR with a statistical significance level of 0.01. For money supply (lnM2) there is no relationship with the economic growth of Lao PDR as well as the analysis in the regression model. For the results of the long-run relationship, it was found that both loan interest rates and money supply have no relationship with economic growth. The analysis of the cause and effect relationship, it was found that only the loan interest rate has an effect on the economic growth of the Lao PDR.